The Moro National Liberation Front, 1972-1978 an annotated bibliography - Domingo, Luis B. (1978)
The Moro National Liberation Front (MNLF) is the main secessionists group fighting for autonomy in Mindanao. It is a sophisticated organization with a central committee, a political bureau, a propaganda and intelligence bureau, provincial/barrio committees, and a regular army.